RUSSIA AND ISLAM: POLITICAL AND ECONOMIC ASPECTS OF THEIR DIALOG - ABZAEVA, Asiyat (CENTRAL ASIA AND THE CAUCASUS, 2006)
Islam is the youngest of the great world religions; as such it imbibed the vast spiritual and intellectual wealth of the preceding epochs. The Muslim world and its theological pillars (monotheism, religion as the Revelation, religion-based ethics, and veneration of Jesus and St. Mary) are much closer to the Christian European legacy than any other of the great world religions. Socially and culturally, however, the Muslim world is far removed from the Christian European legacy because it emphasizes loyalty to the umma rather than the individual’s spiritual life.1 This is a dynamic religion with a rapidly increasing number of followers. Today, one-fifth of the planet’s population follows Islam (1.3 billion), which comes second after Christianity. Muslims live in more than 120 countries of the world. Russia with about 20 million Muslims is one of them.2 There are approximately 50 million Muslims in Central Asia and the Caucasus. In the last quarter of the 20th century, Islam moved to the forefront of world history and confronted mankind with a host of paradoxical problems. Today it attracts much more attention than any other religion; it stirs up heated discussions and contradictory conclusions. This is explained by its sheer size, and its intensive and multisided cooperation with other civilizations. For this reason, a dialog of civilizations should become the prerequisite of a fair world order for the future. The world of Islam is unique; the Muslims can be regarded as a single whole, irrespective of where they live and pray on the planet. Islamic integrity, however, is relative: Islam is both unified and diverse, therefore it is far from being integral for the simple reason that the Islamic nations speak different tongues and have vastly different cultures and customs. Practiced in different countries and regions, this religion is affected by local faiths and traditions and embraces a variety of cultures. Indeed, Islam practiced in Indonesia by the ordinary people has little in common with the faith of the French intellectual proselytes, yet, in the final analysis, it is one and the same Islam. Frederick Denny has rightly pointed out that the Muslims live in at least two cultural environments: the local culture of their native land in which they are born and which they imbibe along with their mothers’ milk, and Islam and the Muslim culture acquired and consciously embraced.